Estudio del delito de femicidio desde una perspectiva criminológica para su prevención y el fortalecimiento de las políticas públicas y normativas - Ambrossi Camacho, Maren Stefanía (2024)
The present Curricular Integration Work is titled "The Study of Femicide from a Criminological Perspective for its Prevention and the Strengthening of Public Policies and Regulations", and its interest lies in investigating and conducting a study on the crime of femicide, the types of violence that lead to its execution, and a detailed analysis of the risk factors obtained from legal science of criminology. These factors contribute to the perpetuation of the crime of femicide because they evidence the violation of the right to life and other inherent rights within a gender context, a direct violation of rights towards women. The study conducted shows that girls, women, and elderly women who were victims of the crime of femicide within Ecuadorian territory were previously victims of gender-based violence in any of its manifestations. Due to lack of information, lack of support networks, or even due to the normalization of gender-based violence within the family environment and society itself, many times it has ended in this fatal outcome, which is the crime of femicide. Therefore, with this research, it is hoped to guarantee better development of prevention measures, equal opportunities for women, and the circulation of information regarding gender-based violence and its irreversible maximum expression, femicide, because education forms the strongest pillars of a gender equality ideology within any society. In the present Curricular Integration Work, methods and techniques were used and applied to allow its development. Surveys and interviews were conducted with legal professionals in gender matters, whose results served to propose the elaboration of respective propositional guidelines, with the aim of guaranteeing the fulfillment of the right to life, and related to this, the right to personal integrity, the right to personal freedom, the right to a life free of violence, the right to equality and non-discrimination, and the right to information, all of which are violated in the course of the iter criminis of the crime of femicide.